Desain Laboratorium Pendidikan Berbasis Keterampilan Literasi Digital - Adhi Setiyawan (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2021)
Digital literacy skills in learning services are needed during the COVID-19 Pandemic. The application of digital literacy in learning requires the support of long-term support unit stability. Many researchers have applied computers and information to improve learning, but research on supporting components and laboratory correlations as a support for the long-term stability of digital literacy is still scarce. The laboratory as a supporting unit has a strategic role in the development of digital literacy-based instructional services. This paper aims to conceptualize an Education Laboratory based on digital literacy skills in Indonesia. The concept of an educational laboratory is constructed using qualitative research methods through exploration involving the components of Lecturers, Schools, Students, and Pranata Lab, Department, and Faculties. The integrative framework for digital literacy at the micro and macro laboratory levels is the core of the discussion. The two basic strategies in this paper are the first strategy of the corelasional framework. The second strategy is regarding the conceptualization of the laboratory which is reduced to the function and scope of the laboratory. The findings of this paper are the Conceptualization of Educational Laboratories as academic support, research facilities, and public facilities. Abstrak: Keterampilan literasi digital dalam layanan pembelajaran sangat dibutuhkan pada masa Pandemi COVID-19. Penerapan literasi digital pada pembelajaran membutuhkan dukungan stabilitas unit pendukung jangka panjang. Banyak peneliti telah mengaplikasikan komputer dan informasi dalam perbaikan pembelajaran, Namun penelitian komponen pendukung dan korelasi laboratorium sebagai pendukung stabilitas jangka panjang literasi digital masih langka. Laboratorium sebagai unit penunjang memiliki peran strategis dalam perkembangan layanan instruksional berbasis literasi digital. Makalah ini bertujuan mengonseptualisasi Laboratorium Pendidikan berbasis keterampilan literasi digital Perguruan Tinggi dan sekolah/madrasah. Konsep laboratorium pendidikan dikonstruk melalui metode penelitian mix method melalui penelitian korelasional dan eksplorasi melibatkan Dosen, Sekolah, Mahasiswa dan Pranata Laboratorium, Program studi dan Fakultas. Kerangka kerja integratif tingkatan mikro dan makro menjadi inti pembahasannya. Dua strategi dasar makalah ini adalah pertama korelasional. kedua konseptualisasi laboratorium yang direduksi menjadi fungsi dan ruang lingkup laboratorium. Temuan makalah ini adalah konsep laboratorium pendidikan sebagai pendukung akademik, fasilitas penelitian, dan layanan publik.